The Mu3e experiment - Berger, Niklaus (Nuclear physics. Proceedings supplements, 2014)
The Mu3e experiment is designed to search for charged lepton flavour violation in the process μ+→e+e−e+ with a branching ratio sensitivity of 10−16. This requires a detector capable of coping with rates of up to 2⋅109 muons/s whilst being able to reduce backgrounds from accidental coincidences and the process μ+→e+e−e+ν¯μνe to below the 10−16 level. The use of 50μm thin high-voltage monolithic active pixel sensors in conjunction with an innovative tracking concept provide the momentum and position resolution necessary, whilst the timing resolution is provided by a combination of scintillating fibres and tiles. The recently approved Mu3e experiment will be located at the Paul Scherrer Institute in Switzerland and is currently preparing for detector construction.